Activation in M1 but not M2 Macrophages Contributes to Cardiac Remodeling after Myocardial Infarction in Rats: a Critical Role of the Calcium Sensing Receptor/NRLP3 Inflammasome - Liu, Wenxiu; Zhang, Xin; Zhao, Meng; Zhang, Xiaohui; Chi, Jinyu; Liu, Yue; Lin, Fang; Fu, Yu; Ma, Dandan; Yin, Xinhua (Cellular physiology and biochemistry, 2015)
Aims: Macrophage (MΦ) infiltration during myocardial infarction (MI) amplifies cardiac inflammation and remodeling. We investigated whether activation of the NRLP3 inflammasome by a calcium sensing receptor (CaSR) in MΦ subsets contributes to cardiac remodeling following MI. Methods and Results: Infiltrated MΦ exhibited biphasic activation after MI; M1MΦ peaked at MI 3d and decreased until MI 14d, whereas M2MΦ peaked at MI 7d and decreased at MI 14d as shown via immunohistochemistry. IL-1β co-infiltrated with both M1MΦ and M2MΦ; IL-1β exhibited the same infiltrating tendency as M1MΦ, which was detected by immunohistochemistry. Increasing ventricular fibrosis was confirmed by Masson staining. CaSR and NLRP3 inflammasome in the MI group were upregulated in MΦ subsets in myocardium and peritoneal MΦ (p-MΦ) compared with the sham groups which were detected by immunofluorescence and western blotting. CaSR-activated NLRP3 inflammasome played a role in M1MΦ via PLC-IP 3 but did not play a role in M2MΦ which were polarized by the THP-1 as shown by western blotting and intracellular calcium measurement. CaSR/NLRP3 inflammasome activation in M1MΦ led to the following effects: upregulated α-sma, MMP-2 and MMP-9, and collagen secretion; and downregulated TIMP-2 in cardiac fibroblasts via IL-1β-IL-1RI, which was detected by coculturing M1MΦ and cardiac fibroblasts. Conclusions: We suggest that the CaSR/NLRP3 inflammasome plays an essential role via the PLC-IP 3 pathway in M1MΦ to promote cardiac remodeling post-MI in rats, including accelerated cardiac fibroblast phenotypic transversion, increased collagen and extracellular matrix (ECM) secretion; however, the CaSR/NLRP3 inflammasome does not play a role in this process in M2MΦ.